Literature Review : Hubungan Pola Makan Dengan Kejadian Anemia Pada Remaja Putri - Nindi Mubarokatun Nafisah; Salafas, Eti (Journal of Holistics and Health Science, 2021)
Anemia in adolescents can have an impact on decreased work productivity, stunted growth, the body is susceptible to infection, resulting in reduced body fitness, decreased enthusiasm for learning and achievement. The onset of anemia can be caused by wrong, irregular and unbalanced dietary intake with adequate nutritional sources what the body needs. The purpose of this study was to determine the correlation between the pattern and the incidence of anemia among female adolescents using a meta-analysis approach. This type of research is a meta-analysis research with a systematic review method, using 5 research journals as data sources that will be used in compiling the results consisting of 1 international journal, 4 national journals accredited by Sinta 4 and indexed by Garuda. The results of the study from a review of 5 articles showed that there was a relationship between diet and anemia in adolescent girls. The similarities of the five journals are in terms of type of research, research methods, data analysis, adolescent research respondents, and research instruments (in the form of a questionnaire). The results of the review through 5 related articles, most of the results showed that the diet of young women was not good and experienced anemia. The differences between each journal were the sampling technique, and the question indicators in the questionnaire were different from one journal to another. Abstrak Anemia pada remaja dapat berdampak pada menurunnya produktivitas kerja, pertumbuhan terhambat, tubuh mudah terinfeksi, mengakibatkan kebugaran tubuh berkurang, semangat belajar dan prestasi menurun.Timbulnya anemia dapat disebabkan oleh asupan pola makan yang salah, tidak teratur dan tidak seimbang dengan kecukupan sumber gizi yang dibutuhkan tubuh. Tujuan penelitian ini untuk mendapatkanhubungan polamakandengan kejadian anemiapadaremajaputridengan menggunakan pendekatan meta analisis.Jenis penelitian adalah penelitian meta analisis dengan metode literature review, menggunakan 5 jurnal penelitian sebagai sumber data yang akan digunakan dalam penyusunan hasil terdiri dari 1 jurnal internasional, 4 jurnal nasional terakreditasi Sinta 4 dan terindex Garuda. Hasil penelitian dari review 5 artikel menunjukkan bahwa ada hubungan pola makan dengan kejadian anemia pada remaja putri. Persamaan dari kelima jurnal yaitu dari segi jenis penelitian, metode penelitian, analisis data, respondenpenelitianyaituremaja, dan inttrumen penelitian (berupa kuesioner). Hasil review melalui 5 artikel terkait, sebagian besar hasil penelitian menunjukkan pola makan remaja putri tidak baik dan mengalami anemia.Perbedaan dari masing-masing jurnal yaitu dari teknik pengambilan sampel, dan indikator pertanyaan dalam kuesioner antara satu jurnal dengan lainnya berbeda.